QUALITY MANAGEMENT OF ELEMENTARY SCHOOLS BASED ON NATIONAL ASSESSMENT - Debie Elvan Latuharhary; Tanwey Gerson Ratumanan; Paul Arjanto (SOSIOEDUKASI, 2026)
This study aims to analyze elementary school quality management based on National Assessment results in three different institutional contexts in Dobo, Aru Islands Regency. The research employed a qualitative multi-site study at SD Naskat Yos Sudarso 1 Dobo, SD Negeri 7 Dobo, and SD Kristen 1 Dobo. Data were collected through in-depth interviews, open observation, and document study involving principals, teachers, school operators, and supervisors. The data were analyzed using reduction, display, and conclusion drawing, followed by cross-site analysis. The findings show that all three schools have implemented quality management through planning, implementation, evaluation, and follow-up, but with different levels of effectiveness. SD Naskat Yos Sudarso 1 Dobo demonstrated a more systematic data-based planning process through the use of Education Report Card data in school programs, supported by literacy habituation, reading corners, literacy competitions, and the GASING method for numeracy. SD Kristen 1 Dobo showed initial efforts to use National Assessment data, although monitoring and follow-up were not yet consistent. SD Negeri 7 Dobo still faced major challenges in integrating assessment data into school planning and instructional improvement. The study concludes that successful quality management based on National Assessment is strongly influenced by data-driven principal leadership, teacher involvement in reflective culture, and consistent evaluation and follow-up mechanisms.